Fabrication and Mechanical Testing of Ultralight Folded Lattice-Core Sandwich Cylinders. (February 2020) - Li, Wanxin; Zheng, Qing; Fan, Hualin; Ji, Bin
Abstract: In this research, two novel folded lattice-core sandwich cylinders were designed, manufactured, and tested. The lattice core has periodic zigzag corrugations, whose ridges and valleys are directed axially or circumferentially. Free vibration and axial compression experiments were performed to reveal the fundamental frequency, free vibration modes, bearing capacity, and failure mode of the cylinder. A folded lattice core effectively restricts local buckling by reducing the dimension of the local skin periodic cell, and improves the global buckling resistance by enhancing the shear stiffness of the sandwich core. The cylinders fail at the mode of material failure and possess excellent load-carrying capacity. An axially directed folded sandwich cylinder has greater load-carrying capacity, while a circumferentially directed folded sandwich cylinder has higher fundamental frequencies. These two types of folded lattices provide a selection for engineers when designing a sandwich cylinder requiring strength or vibration. This research also presents a feasible way to fabricate a large-dimensional folded structure and promote its engineering application.